PENGEMBANGAN SUSU SEGAR DALAM NEGERI UNTUK PEMENUHAN KEBUTUHAN SUSU NASIONAL - Miftah Farid; Heny Sukesi (Buletin Ilmiah Litbang Perdagangan, 2011)
Milk is one of the important foods for fulfilling nutrition needs. There is a wide gap between milk production and consumption. In 2002-2007, fresh milk production only grew by 2 percent; but the consumption rose by 14percent. This paper uses a descriptive analysis to explain policy and program needed by the government to develop a milk development plan. In addition, it provides material for improving coordination among government institutions. On farm level, farmers need technical assistant through government programs and Corporate social Responsibility (CSR), facilitation grass fields, and import facilitation of cows. On marketing level, government plays a very important role in creating a captive market for spreading domestic fresh milk market, evaluating the possibility of milk processing industry to be obliged to purchase domestic fresh milk, improving capital access, and improving mutual cooperation among farmers, and among milk processing firms.